Induced Antileukemic Activity after Blast Modulation is Independent from Immune Checkpoint Marker Expression on Patients’ Blasts or T Cells - Amend, Carina; Weinmann, Melanie; Amberger, Daniel Christoph; Schwepcke, Christoph; Doraneh-Gard, Fatemeh; Krämer, Doris Maria; Schmid, Christoph; Rank, Andreas; Schmetzer, Helga Maria (Archives of Clinical and Biomedical Research, 2025)
Background: Acute myeloid leukemia is still associated with a poor prognosis. New therapeutic strategies are necessary. Myeloid leukemic blasts can be converted into dendritic cells (DC) of leukemic origin leukemiaderived DC (DCleu) using ‘DC-generating Picis’ or ‘DC-generating Kits’, resulting in enhanced leukemia-specific antileukemic immune responses. Methods: DC/DCleu were generated out of leukemic Peripheral Blood Mononuclear Cells (PBMNC) or whole blood (WB) using DC/DCleu- generating protocols and used to stimulate T cell enriched immunoreactive cells in mixed-lymphocyte culture (MLC), followed by a cytotoxicity fluorolysis assay (CTX). We evaluated the expression profiles of immune checkpoint molecules (CD279 (PD-1), CD273 (PD-L2) and CD274 (PDL1)) on uncultured blasts and T cells from AML patients respectively on monocytes and T cells from healthy donors after MLC with Kit pre-treated WB and correlated immune checkpoint (CP) expressions with patients’ clinical data and functional cytotoxicity. Results: We were able to generate DC/DCleu from leukemic (and healthy) PBMNC and WB without induction of blast proliferation. Stimulation of immunoreactive cells after MLC with Kit pre-treated DC/DCleu containing WB resulted in downregulated CP expression on blasts and DCleu and in increased anti-leukemic cytotoxicity. CP expressing T cells (T279+) correlated negatively with response to induction therapy and with improved blasts lysis ex vivo (T274+). Conclusion: Through this immunomodulatory approach, we demonstrated the potential to induce or enhance leukemia-specific and anti-leukemic activity ex vivo, largely independent of checkpoint inhibitor expression on blasts, T cells, or patients’ clinical characteristics. Building on these findings, our data further suggest that DC/DCleu could be generated ex vivo using ‘DCgenerating Picis’ or ‘DC-generating Kits’ for subsequent adaptive transfer to patients, or that in vivo treatment with Kit-M could be explored to help stabilize remissions in AML patients.